Prevalence of antinuclear antibodies in inflammatory bowel disease and seroconversion after biological therapy. (March 2022) - García, María José; Rodríguez-Duque, Juan Carlos; Pascual, Marta; Rivas, Coral; Castro, Beatriz; Raso, Sandra; López-Hoyos, Marcos; Arias-Loste, María Teresa; Rivero, Montserrat
Background: Estimates of detectable antinuclear antibodies (ANA) prevalence vary widely, from 6% in healthy populations to 50–80% in patients with autoimmune disease. However, there is a lack of evidence about the overall prevalence in inflammatory bowel disease (IBD) and ANA seroconversion after the beginning of biological therapy. Objectives: The aim of the study was to investigate the overall prevalence of ANA in IBD patients, their relationship with different treatments, clinical outcomes and the seroconversion rate of ANA in patients treated with biological therapy. Methods: Ambispective observational study including all consecutive IBD patients was carried out. Information about the presence of ANA, disease phenotype, duration, activity, complications, and past and current treatments were transversally collected. Retrospectively, in patients with detectable ANA, data regarding previous ANA detection and the diagnosis of lupus-like syndrome (LLS) was gathered. Results: A total of 879 IBD patients were included. We observed a detectable ANA prevalence of 13.6%. The presence of ANA was frequently associated with biological therapy (36/118) and decreased when immunomodulators were combined to this therapy (7/32). Of 78 patients with ANA prior to the beginning of biological therapy, a seroconversion rate of 28.8% was observed after a mean of 3.14 years. Only 1 patient suffered LLS. Conclusion: Our study showed a prevalence of detectable ANA higher than the expected in healthy population. The presence of ANA was lower when immunomodulator therapy is associated. The ANA seroconversion rate is relevant after the initiation of biological treatment nevertheless, the risk of LLS appeared to be marginal.